Whole body adhesion: hierarchical, directional and distributed control of adhesive forces for a climbing robot - Sangbae Kim; Spenko, M.; Trujillo, S.; Heyneman, B.; Mattoli, V.; Cutkosky, M.R. (Proceedings 2007 IEEE International Conference on Robotics and Automation, 2007)
We describe the design and control of a new bio-inspired climbing robot designed to scale smooth vertical surfaces using directional adhesive materials. The robot, called Stickybot, draws its inspiration from geckos and other climbing lizards and employs similar compliance and force control strategies to climb smooth vertical surfaces including glass, tile and plastic panels. Foremost among the design features are multiple levels of compliance, at length scales ranging from centimeters to micrometers, to allow the robot to conform to surfaces and maintain large real areas of contact so that adhesive forces can support it. Structures within the feet ensure even stress distributions over each toe and facilitate engagement and disengagement of the adhesive materials. A force control strategy works in conjunction with the directional adhesive materials to obtain sufficient levels of friction and adhesion for climbing with low attachment and detachment forces.